Henkivakuutusvaje suomessa suuruusluokan arviointia yksilöaineistoilla - Olli Ropponen; Tero Kuusi; Tarmo Valkonen (The Research Institute of the Finnish Economy (ETLA), 2022)
This report employs individual-level register data to study the coverage and amounts of voluntary term life insurances, the monetary losses following from the death of a breadwinner, and the life insurance gap arising as the difference of the two. The data include information on the life insurances of Finnish individuals and their individual and household level information between 2018 and 2020. We find that 8 % of the individuals have at least one type of term life insurance in the data. For them the average life insurance is 73 000 exteuro. The take up of life insurances differ between groups, and it is more frequent among working-age, married and higher income individuals. The life insurance gap calculations account for a number of changes in living standards following from a death of a breadwinner, including those in household income, consumption, existing wealth, survivors' pensions and life insurances. For those individuals who have earned income and who live in families consisting of at least two persons the average life insurance gap is between 65 000 exteuro and 70 000 exteuro. This is the amount of additional life insurance that would retain the consumption possibilities the same as before the breadwinner's death. For those who have a voluntary life insurance the gap is on average close to zero. Therefore, the life insurance gap arises mainly among those people not having a life insurance at all.
Keywords: G22; H31; H55; J17; 330; Life insurances; Life insurance gap; Households; Social security; Forgone income